Nutritional Quality of Opuntia ssp. at Different Phenological Stages: Implications for Forage Purposes - Silva, Danilo Dantas da; Andrade, Albericio Pereira de; Silva, Divan Soares da; Alves, Francisco Abel Lemos; Valença, Roberta de Lima; Santos, Djalma Cordeiro dos; Medeiros, Ariosvaldo Nunes de; Araújo, Fernando dos Santos; Lima, Lucas Kennedy Silva; Bruno, Riselane de Lucena Alcantara (Journal of Agricultural Studies, 2022)
The study aimed to evaluat the chemical composition of forage cactus cladodes of the genus Opuntia spp. at different stages of phenological development. The experiment was conducted in a completely randomized design, with a 4×3 factorial scheme, with four species of cactus (Opuntia stricta Haw, Opuntia undulata Griffiths, Opuntia atropes Rose and Opuntia larreri FAC Weber) and three stages of cladode development (young, intermediate, and mature). The chemical composition of Opuntia cladodes varied according to species and phenological stage. Dry matter (DM), neutral detergent fiber (NDF) and acid detergent fiber (ADF) concentrations increased, and crude protein (CP) decreased with cladode maturation. The species O. atropes had the lowest levels of organic matter (OM), CP, total carbohydrates, and non-fibrous carbohydrates, as well as the highest values of mineral matter, NDF and ADF. Calcium and phosphorus contents increased with cladodium maturation. The concentrations of boron, copper and manganese were higher in the young and intermediate stages. The cladodes of O. stricta, O. undulata and O. larreri showed better nutritional quality for feeding domestic ruminants. Young and intermediate cladodes are more proteinaceous and less fibrous. These results can be useful in selecting the forage cactus species and in optimizing the use of cladodes for feeding different categories of ruminants in semiarid regions.